Pembangunan Game Analysis Training terhadap Peningkatan Kemampuan Berpikir Induktif pada Siswa Tingkat SMP menggunakan Speech Recognition (Studi Kasus: SMPS YKPP Sungai Pakning) - Heri Sasmita; Wenda Novayani (Journal of Applied Informatics and Computing, 2020)
Inductive reasoning is a way to take general conclusions from individual cases. Mathematical reasoning is one of the main abilities that needs to have. Through human reason, humans continue to develop and improve their ability to adapt on dynamic environment and create technologies that can facilitate their lives. Based on direct interviews with the YKPP Junior High School Mathematics Teacher, revealed that there are still many students who are still not good in the ability to think inductively, and if this ability is not trained, it will affect the child's academic value, especially in mathematics. Then based on the results of direct interviews with clinical psychologists, solutions are prepared using the IST and IRT forms to be able to practice the ability to think inductively in children aged 12-15 years which age is in accordance with the range of junior high school age children. Many learning media developed at this time as supporters of conventional learning media. Learning methods with Educational Game media are believed more better compared to conventional learning methods. Therefore, Game Analysis Training has been made using the IST and IRT forms, which can help students improve their ability to think inductively. The material used in this game has passed validation test by Dra. Erni Yulial S. Psi, who is a clinical psychologist in Pekanbaru City. This statement is assisted by the results of pre-test and post-test that have been done, where an increase in the results of post-test conducted with the percentage of correctly is 13.8% for the Intelligenz Structure Test form and 8.28% for the Inductive Reasoning Test form.